PERSONAL DEVELOPMENT EXPERT: THEORETICAL ANALYSIS OF THE PROBLEM - Filonenko, M. (Continuing Professional Education: Theory and Practice, 2019)
Studied Condition of theoretical approaches to personal development expert. Analyzed the psychological and pedagogical literature with definite problem. Theoretical analysis approaches, concepts and models of personal development allowed to conclude that personal development is in accordance with professional features and patterns of overall mental development. Analysis of the concept allowed us to approach the understanding of the underlying factors of formation of medical students during their studies at the university in the form of the following provisions: student-activity-orientation of content, methods, organization of educational process; formation of personal and professional settings; conceptual unity and continuity of content, forms and methods of teaching at the university; problem-oriented, evolving nature of the process of obtaining medical education; close link theory and practice; open educational process of innovation; subject-subject relationship faculty and medical students; attract higher medical and psychological services for the development of the individual students, providing them with psychological help if needed and more. Identify the main stages of personal development of medical student, which may contribute to the development of a general concept of dialectics personal development expert in learning in higher education. It was considered self characteristics that have a direct impact on personal development expert.